2006
DOI: 10.1017/s1740022806000155
|View full text |Cite
|
Sign up to set email alerts
|

The Spanish Empire and its legacy: fiscal redistribution and political conflict in colonial and post-colonial Spanish America

Abstract: The comparative history of the Americas has been used to identify factors determining longterm economic growth. One approach, new institutional economics (NIE), claims that the colonial origins of respective institutional structures explain North American success and Spanish American failure. Another argues that differences in resources encountered by Europeans fostered divergent levels of equality impacting on institutions and growth. This paper challenges the theoretical premises and historical evidence of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 44 publications
0
34
0
1
Order By: Relevance
“…13 In the case of the Spanish empire, recent work has shown that the bulk of financial transfers were between colonies rather than to the metropole. This is part of a general challenge to North American interpretations of the Spanish empire as simply extractive (Grafe and Irigoin, 2006). For a later period of Spanish history, Domenech (2008, this issue) also questions the relalionship between extraction and the rate of development.…”
Section: Colonial Rule and African Economiesmentioning
confidence: 99%
“…13 In the case of the Spanish empire, recent work has shown that the bulk of financial transfers were between colonies rather than to the metropole. This is part of a general challenge to North American interpretations of the Spanish empire as simply extractive (Grafe and Irigoin, 2006). For a later period of Spanish history, Domenech (2008, this issue) also questions the relalionship between extraction and the rate of development.…”
Section: Colonial Rule and African Economiesmentioning
confidence: 99%
“…Brule 2009;Alston et al 2009). In a different vein, social and economic historians have also produced, as it would be expected, a considerable body of research on topics with a direct relevance to the issues under review, such as agriculture and land tenure (Assadourian 2006;Banerjee and Lakshmi 2005), plantation economy (Schwartz 2004), land, credit and labour markets (Swami 2011;Boomgard 2009), and fiscal issues (Travers 2004;Grafe and Irigoin 2006), just to mention a few.…”
Section: Contents | íNdicementioning
confidence: 99%
“…32932). Regina Grafe and Alejandra Irigoin (2006) have coined the term "bargained absolutism" for the second half of the eighteenth century, emphasizing the still active role played by corporate elites in government. 41 Even if the resulting centralization was not absolute, the argument still stands that the role of the central government in fiscal collection and enforcement increased to unprecedented levels, and that such increase was more pronounced in the regions where the corporate elites were more dependent on the Crown for economic rents and privilege.…”
Section: Increase In Fiscal Centralizationmentioning
confidence: 99%